Examining Commercialized Security Industry’s Services on National Security in Nairobi County, Kenya - Mutonyi, Gerald; Ann Merecia Sirera; Mwai, Wangari (Technium Social Sciences Journal, 2020)
Maintenance of security and good order for the citizens, had traditionally been undertaken by the state. However, non-state actors have come up to offer security to those who can afford to pay for it. And this is the liberalists view of the provision of security that, the pursuance of security can be achieved with the involvement of other actors offering the same. Despite this development, few studies have examined commercialized security industry services on national security in Kenya. Using Security Governance theory and Network Analysis theory, this study sought to understand the topic. The study took on a cross sectional survey design, and was carried out in Nairobi with the adult residents as the target population. A multistage sampling technique was employed to obtain the respondents. Questionnaires, scheduled interviews and structured observation were used to collect data. The Statistical Package for Social Sciences (SPSS version 25, 2017) was used in data management and analysis. The results demonstrate that (1) Manned guarding significantly contributes to the 26 % of outcome of the commercialized security B = .260, ? = .135, P = .007; (2) Alarm and Electronics 22.9 %; B = .229, ? = .224, P = .001; (3) CVIT security service contributes significantly and positively at 10.8 %; B = .108, ? = .118, P = .018. While commercial investigative security service 3.6 % (B = .036, ? = .084, P < = .103 although it was not significant. The study concluded that, commercialized security though motivated by profit making plays a significant role that enhances state capacity in provision of security as well as contributes to safety of citizens. Thus the study recommended that, there should be efforts to increase the usage of commercialized security investigation service. It is expected that the findings of this research will provide data that can be used to inform policy and practice amongst commercial security providers to increase their impact on national security in Kenya. The data can also stimulate the academic community towards more research in the field.